2019
DOI: 10.1139/apnm-2018-0485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energy-matched high-intensity interval and moderate-intensity continuous exercise sessions on latency to eat, energy intake, and appetite

Abstract: High-intensity interval exercises (HIIex) have gained popularity but their effects on eating behavior are poorly known. The aim of this study was to evaluate whether the effects of HIIex on the 3 main components of eating behavior (appetite, intake, and latency to eat) differ from those of moderate-intensity continuous exercises (MICex) for the same energy expenditure. Fifteen young normal-weight males completed 3 sessions in a counterbalanced order: HIIex (30-s bouts at 90% of maximal oxygen uptake interceded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Another recent study by Charlot and Chapelot recruited 15 healthy men who exercised regularly to perform HIIE consisting of 13 sets of 90% VO 2 max exercise for 30 s and 35% VO 2 max exercise for 60 s (total exercise time: 20 min), moderate-intensity continuous exercises (MIE; 42% VO 2 max for 40 min), and the sedentary rest control trial (REST). The results showed that no change occurred in subjective appetite and energy intake, but HIIE delayed their meal by nearly 20 min compared to MIE [40]. The results from the above studies suggest that exercise intensity has a significant effect on appetite hormonal responses and subjective appetite.…”
Section: The Impact Of the High-intensity Exercise Challenge On Appet...mentioning
confidence: 78%
“…Another recent study by Charlot and Chapelot recruited 15 healthy men who exercised regularly to perform HIIE consisting of 13 sets of 90% VO 2 max exercise for 30 s and 35% VO 2 max exercise for 60 s (total exercise time: 20 min), moderate-intensity continuous exercises (MIE; 42% VO 2 max for 40 min), and the sedentary rest control trial (REST). The results showed that no change occurred in subjective appetite and energy intake, but HIIE delayed their meal by nearly 20 min compared to MIE [40]. The results from the above studies suggest that exercise intensity has a significant effect on appetite hormonal responses and subjective appetite.…”
Section: The Impact Of the High-intensity Exercise Challenge On Appet...mentioning
confidence: 78%
“…The relationship between EE and EI has been shown to depend predominantly on exercise intensity [22]. High-intensity exercise (≥70% VO 2max ) has been shown to decrease REI, hunger rating and increase volitional onset of eating [22,23]. However, the pattern of eating behavior seems to be sex-specific, with appetite sensations being decreased in men [22] in response to strenuous exercise whereas women do not show these modifications in appetite sensations [24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that acute HIIE stimulates anorexigenic signals that could reduce energy intake for few hours 16 . However, comparison of HIIE and MICE effects on short‐term post‐exercise perceived appetite showed higher, 36 similar, 16 or no reduction 37 of the appetite score by HIIE. In our study, the perceived appetite score during the 2‐hour recovery period (AUC data) was lower after HIIE 1 and HIIE 2 than MICE.…”
Section: Discussionmentioning
confidence: 99%